KINERJA DINAS LINGKUNGAN HIDUP DALAM PENGELOLAAN SAMPAH DI KOTA MANADO - WAHYUNI, SRI; TAMPI, GUSTAAF BUDI; MAMBO, RULLY (JURNAL ADMINISTRASI PUBLIK, 2017)
Abstract: Population and community dietary changes cause the increase of the volumes of type, and characteristic of theincreasingly diverse garbage waste management. Based on the problems of Research aims to know the performance ofthe Department of the environment in the waste management in the city of Manado.This study uses qualitative methods with selected informants consisting of Chairman, officials of the competent officials/staff/ implementation, and how the garbage workers in the service of the Environment Manado as well as the community.Data collection techniques used are interviews, observation and documentation. Qualitative data were analysed withdescriptive narrative supported by primary and secondary data.The results showed that the performance of the related Department of the environment in the waste management in the cityof Manado has shown a fairly good results, in terms of productivity can be seen already very good views of the goals set andthe effort to realize the goal, among others, with the application of law socialization, adds to the operational personnelhygiene and the granting of construction on the importance of environmental hygiene in order to materialize the city ofManado in a healthy, comfortable, clean, healthy and free of waste by improving the quality of service sothat waste treatment system Manado city becomes "Cendikia" and as a destination "Ecotourism". Similarly, whenviewed from the responsivitas against the incoming complaints from community directly dealt with up with a sprightly,assertive and sociable and friendly also responds when serving. The same thing can also be seen in the responsibility,because the procedure of the Ministry of the environment Office of trash in Manado city is already organised properly. Inaddition to accountability is already good enough in this the role of Government as a provider of basic services and wastemanagement facilities as well as briefing policymakers also firmly related environment and garbage. BesidesGathering information dissemination and community aspirations regarding waste processing services through socializationand dropped directly into the field, conduct of meetings between the device and the public, as well as throughprint/online media others. But in terms of the quality of service is still lacking good especially the willingness of wastemanagement infrastructure and facilities because it looked to the future production of garbage will be moreand more, socialization and interaction of related problems of garbage as well as the affirmation of a rule about garbage isstill lacking.Keywords: performance, waste management